PERTUMBUHAN DAN KELANGSUNGAN HIDUP LARVA IKAN BETOK (Anabas testudineus) YANG DIBERI PENCAHAYAAN DENGAN LAMA WAKTU BERBEDA - Fultri Miranti; Muslim .; Yulisman . (Universitas Sriwijaya, 2017)
ABSTRACT Climbing perch (Anabas testudineus) is a kind of swamp fish which is potentially to be cultivated. Photoperiod is one of factor that influence growth from culture fish larvae. Light also influence growth hormone and make larvae easier to eat their feed because larvae usually visual feeder. The aim of this research is to determine the best photoperiod in larvae of age 3 – 27 days so as to generate growth and survival rate climbing perch of larvae highest in aquarium with defferent of photoperiod. The usage of the research are expected that different photoperiod can influence the growth and survival of climbing perch larvaes. The research was conducted on April - May 2016 in Laboratory of Budidaya Perairan, Faculty of Agriculture, Sriwijaya University. This research methods used completely randomized design (CDR) with use six treatments and three replications of photoperiod those are P1(24L:0D), P2(18L:6D), P3(12L:12D), P4(6L:18D), P5(0L:24D). The parameters of this research are growth, survival rate of climbing perch larvae and maintenance of water quality. The result showed that photoperiod has significant effect of survival rate, weight growth and length growth from climbing perch photoperiod for 24 hours each day (treatments P1) has the highest result for survival rate and growth 81.11%±2.01%, 30.68mm±0.14mm, 0.46g±0.04g. The value of water quality during larvae rearing were temperature 27 – 31 oC, pH 5.70 – 7.10, dissolved oxygen 4.56 – 7.58 mg.L-1 and ammonia 0.02 – 0.11 mg.L-1. Keywords: Climbing perch, Growth, Photoperiod, Survival rate